2013
DOI: 10.1007/s12032-013-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of MIP-1alpha correlate with bone disease and angiogenic cytokines in patients with multiple myeloma

Abstract: Many cytokines possess variable roles in the pathogenesis of multiple myeloma. Macrophage inflammatory protein-1alpha (MIP-1alpha) is an osteoclast-activating factor with a major role in myeloma bone disease. The aim of the study was to examine its participation in the angiogenic process of the disease. We measured, by enzyme-linked immunosorbent assays, its serum levels in 56 newly diagnosed myeloma patients, in several skeletal grades and stages of the disease and in 25 healthy controls. Concurrently, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Elevated levels of cytokines have also been described in other hematological malignancies including chronic myeloid leukemia (CML), non-Hodgkin lymphoma, multiple myeloma and myelodysplastic syndromes. 11 , 12 , 13 , 14 , 15 , 16 Moreover, the high plasmatic levels of inflammatory cytokines are associated with the response of CML patients to tyrosine-kinase inhibitors and with the prognosis of the aforementioned hematological malignancies. 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of cytokines have also been described in other hematological malignancies including chronic myeloid leukemia (CML), non-Hodgkin lymphoma, multiple myeloma and myelodysplastic syndromes. 11 , 12 , 13 , 14 , 15 , 16 Moreover, the high plasmatic levels of inflammatory cytokines are associated with the response of CML patients to tyrosine-kinase inhibitors and with the prognosis of the aforementioned hematological malignancies. 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Using microarray, we identified that the most highly upregulated gene following HIF-2a overexpression in LP-1 cells was the chemokine receptor CCR1. CCR1 has previously been suggested to play an important role in multiple myeloma with the levels of the CCR1 ligand CCL3 being elevated in the peripheral blood of multiple myeloma patients with advanced disease (43,44). Notably, CCL3 acts as a potent stimulus for the migration of multiple myeloma cells in vitro (45).…”
Section: Discussionmentioning
confidence: 99%
“…In MM patients, however, RANKL is overexpressed as OPG levels decrease, leading to a disturbed RANKL/OPG balance favoring bone resorption [136]. MM cells also produce MIP-1α, and increased MIP-1α serum levels correlate with lytic bone lesions in MM patients [137, 138]. In addition, the MM cells express and secrete factors that are able to suppress OB differentiation and activity.…”
Section: The Igf System In MMmentioning
confidence: 99%